In Vitro Effects of Cognitives and Nootropics on Mitochondrial Respiration and Monoamine Oxidase Activity - Singh, Namrata; Hroudová, Jana; Fišar, Zdeněk (Molecular neurobiology, 2017)
Impairment of mitochondrial metabolism, particularly the electron transport chain (ETC), as well as increased oxidative stress might play a significant role in pathogenesis of Alzheimer's disease (AD). Some effects of drugs used for symptomatic AD treatment may be related to their direct action on mitochondrial function. In vitro effects of pharmacologically different cognitives (galantamine, donepezil, rivastigmine, 7-MEOTA, memantine) and nootropic drugs (latrepirdine, piracetam) were investigated on selected mitochondrial parameters: activities of ETC complexes I, II + III, and IV, citrate synthase, monoamine oxidase (MAO), oxygen consumption rate, and hydrogen peroxide production of pig brain mitochondria. Complex I activity was decreased by galantamine, donepezil, and memantine; complex II + III activity was increased by galantamine. None of the tested drugs caused significant changes in the rate of mitochondrial oxygen consumption, even at high concentrations. Except galantamine, all tested drugs were selective MAO-A inhibitors. Latrepirdine, donepezil, and 7-MEOTA were found to be the most potent MAO-A inhibitors. Succinate-induced mitochondrial hydrogen peroxide production was not significantly affected by the drugs tested. The direct effect of cognitives and nootropics used in the treatment of AD on mitochondrial respiration is relatively small. The safest drugs in terms of disturbing mitochondrial function appear to be piracetam and rivastigmine. The MAO-A inhibition by cognitives and nootropics may also participate in mitochondrial neuroprotection. The results support the future research aimed at measuring the effects of currently used drugs or newly synthesized drugs on mitochondrial functioning in order to understand their mechanism of action.
Keywords: Monoamine Oxidase; rivastigmin; Animals; Mitochondrial respiration; Reactive oxygen species; Mitochondria; Oxygen Consumption; Rivastigmine; prasata; Nootropic Agents; memantin; mozek; donepezil; Donepezil; monoaminoxidasa; nootropní látky; mitochondrie; kognice; galantamin; Indans; Brain; Swine; Piperidines; Alzheimer Disease; Cognition; Nootropics; Alzheimerova nemoc; Memantine; Cognitives; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; indany; Monoamine oxidase; piperidiny; spotřeba kyslíku; Galantamine